An assessment of health risks and mortality from exposure to secondhand smoke in Chinese restaurants and bars. - Ruiling Liu (Public Library of Science (PLoS), 2014)
Introduction Smoking is generally not regulated in restaurants or bars in China, or the restrictions are not fully implemented if there are any, while the related hazard health effects are not recognized by the majority of the Chinese population. Objectives This study aims to assess the excess health risks and mortality attributed to secondhand smoke (SHS) exposure in restaurants and bars for both servers and patrons to provide necessary evidence for advancing tobacco control in this microenvironment. Methods Two approaches were used for the assessment. One is a continuous approach based on existing field measurements and Repace and Lowrey's dose-response model, and the other is a categorical approach based on exposure or not and epidemiological studies. Results Based on the continuous approach, servers were estimated to have a lifetime excess risk (LER) of lung cancer death (LCD) of 730 to 1,831×10(-6) for working five days a week for 45 years in smoking restaurants and 1,862 to 8,136×10(-6) in smoking bars, and patrons could have a LER of LCD of 47 to 117×10(-6) due to visiting smoking restaurants for an average of 13 minutes a day for 60 years, and 119 to 522×10(-6) due to visiting smoking bars. The categorical approach estimated that SHS exposure in restaurants and bars alone caused 84 LCD and 57 ischemic heart disease (IHD) deaths among nonsmoking servers and 1,2419 LCDs and 1,689 IHD deaths among the nonsmoking patron population. Conclusions SHS exposure in restaurants and bars alone can impose high lifetime excess risks of lung cancer death and ischemic heart disease deaths to both servers and patrons, and can cause a significant number of deaths each year in China. These health risks and deaths can be prevented by banning smoking in restaurants and bars and effectively implementing these smoking bans.